Mindful monitoring and accepting the body in physical activity mediates the associations between physical activity and positive body image in a sample of young physically active adults - Jankauskiene, Rasa; Baceviciene, Migle (Frontiers in Sports and Active Living, 2024)
Introduction The study aimed to extend research on the possible mechanisms that explain the associations between physical activity (PA), mindfulness during PA and positive body image. In the present study, we tested the mediating role of state mindfulness during PA in the association between PA and trait body appreciation. We also explored the moderating roles of sex and body mass index (BMI) in these associations. Methods In total, 759 students participated in the study but after applying the inclusion criteria 539 questionnaires were approved for analysis, with a mean age of 23.3 ± 7.2 years (49.7% were women). Study participants completed the online survey, which included sociodemographic details, PA data, the State Mindfulness Scale for Physical Activity 2 (SMS-PA-2) and the Body Appreciation Scale 2 (BAS-2). Results Monitoring and accepting the body during exercise mediated the association between PA and body appreciation. BMI moderated the association between accepting the body during exercise and body appreciation: for heavier individuals with BMI > 24.99 kg/m2, the associations between accepting the body during exercise and body appreciation were higher (B = 0.53, p < 0.001) compared to those whose body weight was in the normal range (B = 0.21, p < 0.001). Conclusion Strengthening mindfulness and promoting mindful body acceptance during exercise might enhance a positive body image, especially in individuals with a higher BMI.